(untitled) - MacDonald, Matthew (Beijing, 2011)
Overview: Think you need an army of skilled programmers to build a website? Think again. With nothing more than an ordinary PC, some raw ambition, and this book, you'll learn how to create and maintain a professional-looking, visitor-friendly site. This Missing Manual gives you all the tools, techniques, and expert advice you need. Plan your site: create web pages by learning the basics of HTML and HTML5; Control page design with CSS: format text, images, links, tables, and other elements; Attract visitors: ensure that people can find your site through popular search engines; Build a community: add forums, fresh content, and a feedback form to encourage repeat visits; Get smart: use free tools to identify your site's strengths and weaknesses; Create your own blog: post your musings with a free blog-hosting service; Bring in cash: host Google ads, sell Amazon's wares, or push your own products; Add pizzazz: include audio, video, interactive menus, and more
Keywords: Web sites,Trang web; Design,Thiết kế